A review of bridge scour monitoring techniques - Prendergast, L.J.; Gavin, K. (Elsevier, 2014)
The high profile failure of the Malahide Viaduct in Dublin, Ireland, which is a part of the EU TEN-T network of critical transport links, was caused by foundation scour. Scour is a common soil-structure interaction problem. In light of current changes in climate, increasing frequency of flooding, coupled with the increasing magnitude of these flood events, will lead to a higher risk of bridge failure. Monitoring scour is of paramount importance to ensure the continued safe operation of the aging bridge asset network. Most monitoring regimes are based on expensive underwater instrumentation that can often be subjected to damage during times of flooding, when scour risk is at its highest. This paper presents a critical review of existing scour monitoring equipments and methodologies with a particular focus on those using the dynamic response of the structure to indicate the existence and severity of the scour phenomenon affecting the structure. A sensitivity study on a recently developed monitoring method is also undertaken